Correcting coils in end magnets of accelerators - Kassab, L. R P [UNESP]; Gouffon, P. (American Physical Society (APS), 1998)
We present an empirical investigation of the correcting coils behavior used to homogenize the field distribution of the race-track microtron accelerator end magnets. These end magnets belong to the second stage of the 30.0 MeV cw electron accelerator under construction at IFUSP, the race-track microtron booster, in which the beam energy is raised from 1.97 to 5.1 MeV. The correcting coils are attached to the pole faces and are based on the inhomogeneities of the magnetic field measured. The performance of these coils, when operating the end magnets with currents that differ by ±10% from the one used in the mappings that originated the coils copper leads, is presented. For one of the magnets, adjusting conveniently the current of the correcting coils makes it possible to homogenize field distributions of different intensities, once their shapes are practically identical to those that originated the coils. For the other one, the shapes are changed and the coils are less efficient. This is related to intrinsic factors that determine the inhomogeneities. However, we obtained uniformity of 0.001% in both cases. © 1998 The American Physical Society.